THE IMPACT OF FUNDING RISK ON RISK TAKING COMMERCIAL BANKS IN INDONESIA - Kharis Raharjo; Rita Andini; Dwi Retna Sulistyawati (Jurnal Ekonomi, 2022)
This study aims to determine the impact of funding liquidity risk and profitability on the risk taking of commercial banks in Indonesia. Sampling using purposive sampling technique on the financial statements. The population of this research is 45 banks. The dependent variable in this study is bank risk taking. The independent variables in this study are funding liquidity risk, profitability, liquidity risk, size, efficiency, credit risk, and asset growth. This study uses descriptive statistical analysis and panel data regression analysis. The results of this study find that profitability and credit risk affect bank risk taking, while the variables of funding liquidity risk, liquidity risk, size, efficiency and asset growth have no effect on bank risk taking.